Roots, Region, and Resistance: Facing Industrial Ruin in Sydney, Cape Breton, during Canada’s Centennial Year - Parnaby, Andrew (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2019)
On 13 October 1967 – “Black Friday” – the owners of the Dominion Steel and Coal Company (DOSCO) announced the imminent closure of the company’s Sydney steel works. Yet after a massive community demonstration dubbed the “Parade of Concern,” the provincial government, with significant federal assistance, purchased the plant from DOSCO and turned it into a provincial Crown corporation. This state-centred response to deindustrialization demonstrates the economic, political, and cultural importance of “place” in adverting the collapse of heavy industry, a response that was utterly absent in the American context and used only sparingly in the Canadian one.